Intangible Asset to Improve Firm Value: The Moderating Role of Managerial Ability - Wira, Variyetmi; Lukviarman, Niki; Rahim, Rida; Yonnedi, Efa (Politeknik Negeri Bengkalis, 2024)
This study examines the relationship between intangible assets and firm value moderated by the role of managerial ability. The study used 498 companies from 2012 to 2022 on the Indonesia Stock Exchange. Data was processed using unbalanced panel regression, using Eviews application version 13. The study's results stated that intangible assets have a negative relationship with firm value. Second, managerial ability can positively moderate the relationship between intangible assets and firm value. When managers are able to provide communication and provide good management of intangible assets, it will provide positive value and will be able to increase the contribution of company value. This research implies that the role of managers in managing intangible assets is very important to achieve company value. These results also provide reinforcing evidence on RBV theory that managerial ability is a unique resource capable of creating value and providing a competitive advantagethis purpose.